Estudio de factibilidad para la instalación de una empresa comercializadora de productos cárnicos en la Parroquia San Camilo, Cantón Quevedo, año 2013. - Zambrano Vila, Marjorie Johanna (2013)
The development and implementation of a company has been immersed management process for the planning, organization, direction and control of the activity undertaken, this is where the employer must use the market projection for the purpose of analyzing globally to business environment through an effective technical study, financial and administrative budget to determine the feasibility of installing a marketer of meat products, on the basis of this statement was made this research work in the parish of the canton San Camilo Quevedo, province Los Rios. The objectives were:  Identify the most consumed meat in the market of St. Camillus parish Quevedo Canton, through the survey.  Perform a technical study to understand the machinery that will be needed for installation of the meat trading company in St. Camillus parish.  Make a financial study - economic and sensitivity. For registration information a questionnaire was used to survey two segments of the population: 6 meats local owners and 395 customers to determine their criteria on quality, price, quantity and service. The cash flow generated for the first year is $ 16.484,59 because the initial investment in this year, stabilizing in the second year at $ 18.618,62 then increases sharply in the third, fourth and fifth year with $ 20.838,17; 22.069,40; 23.282,27 and respectively. The net present value presented a positive value which means $ 4.892,23 liquid return generated by the project updates. Therefore the design is feasible. The internal rate of return is 21%, which was higher than the market interest rate, so the project is feasible and viable economically.